Silky: The Woods Cat - Moss, Helen 1922-; Arkinstall, Eva (Austin, Tex. : Eakin Press, 1993)
Miss Kate befriends Silky, a stray cat, and gradually gains her trust and her love.
Keywords: Cats -- Fiction